Measurement of the Ratio between g‐Factors of the Ground States of 87Rb and 85Rb. Issue 5 (21st October 2018) - Mora, Jason; Cobos, Aracely; Fuentes, Dominic; Jackson Kimball, Derek F.
Abstract: The ratio between the Landé g ‐factors of the 87 Rb F = 2 and 85 Rb F = 3 ground‐state hyperfine levels is experimentally measured to be g F ( 87 ) / g F ( 85 ) = 1.4988586 ( 1 ), consistent with previous measurements. The g ‐factor ratio is determined by comparing the Larmor frequencies of overlapping ensembles of 87 Rb and 85 Rb atoms contained within an evacuated, antirelaxation‐coated vapor cell. The atomic spins are polarized via synchronous optical pumping and the Larmor frequencies are measured by off‐resonant probing using optical rotation of linearly polarized light. The accuracy of this measurement of g F ( 87 ) / g F ( 85 ) exceeds that of previous measurements by a factor of ≈50 and is sensitive to effects related to quantum electrodynamics. Abstract : The ratio between ground‐state g ‐factors of rubidium‐87 and rubidium‐85 is measured to be 1.4988586(1), reducing uncertainty by a factor of 50 compared to previous measurements. The experiment uses synchronous optical pumping and probing via optical rotation to measure spin precession of rubidium atoms contained within an antirelaxation‐coated vapor cell. The measurement is sensitive to effects related to quantum electrodynamics.